A base-free copper-assisted synthesis of C2-symmetric spirotelluranes and biaryls based on divergent stoichiometry of Na2Te. Issue 50 (1st June 2022) - Batabyal, Monojit; Jain, Saket; Upadhyay, Aditya; Raju, Saravanan; Kumar, Sangit
Abstract : Herein, we report base free copper(i )-assisted synthesis of C 2 -symmetric spirotelluranes and biaryls based on divergent stoichiometry of Na2 Te. The synthesized spirodiazatelluranes served as a potent catalyst for the reduction of H2 O2 and nitro-Michael reaction. Abstract : A one pot Cu(i )-assisted synthetic methodology has been developed for the preparation of biologically important C 2 -symmetric spirodiaza, benzyloxy and benzoxytelluranes from 2-bromo- N -aryl benzamides, benzyl alcohols, and benzoic acids by using the tellurium dianion (Te 2− ) under base-free conditions. Furthermore, C–C coupled biaryl 1, 1′-diamides have been prepared by using an excess of Na2 Te under the same reaction conditions. The synthesized spirodiazatelluranes served as a potent catalyst for the reduction of H2 O2 and nitro-Michael reactions.